Epoxy thermosets and materials derived from bio-based monomeric phenols: Transformations and performances. (September 2020) - Wan, Jintao; Zhao, Jianqing; Zhang, Xianwei; Fan, Hong; Zhang, Junhao; Hu, Daodao; Jin, Pujun; Wang, De-Yi
Graphical abstract: Abstract: Recent years have witnessed significant progress in bio-based epoxy thermosets. A variety of epoxy thermosets have been synthesized from various bioresources. In particular, epoxy thermosets derived from bio-based monomeric phenols, either naturally occurring or biotransformed, such as cardanol, eugenol, vanillin, tannin acid, gallic acid, and so forth. This review summarizes the research regarding this theme and highlights the molecular transformations and ultimate properties of the resultant epoxy thermosets and materials. The relevant epoxy monomers, prepolymers, curing agents, additives, cured thermosets, functional materials and biocomposites are discussed based on their molecular structures and properties of crosslinked networks. Finally, the challenges and opportunities in developing sustainable epoxy thermosets and materials from bio-based monomeric phenols are presented.